Evaluating the short-term and long-term effects of an internet-based aural rehabilitation programme for hearing aid users in general clinical practice: a randomised controlled trial - Malmberg, Milijana (BMJ Open, 2017)
OBJECTIVE: Guided internet-based intervention beyond hearing aid (HA) fitting has been shown to be efficacious in randomised controlled trials (RCTs). However, internet interventions have rarely been applied clinically as a part of regular aural rehabilitation (AR). Our aim was to evaluate the effectiveness of internet-based AR for HA users from a clinical population. OUTCOME MEASURES: The Hearing Handicap Inventory for the Elderly (HHIE) was used as the primary outcome measure, and the Communication Strategies Scale (CSS) and the Hospital Anxiety and Depression Scale were used as secondary outcome measures. All questionnaires were administered before and directly after the intervention and at 6 months postintervention. METHODS: We used a parallel group design (RCT). The data were collected in 2013–2014 at three different clinics. Seventy-four HA users were randomly assigned to receive either full internet-based AR (intervention group, n=37) or one element of the internet-based AR (control group, n=37). RESULTS: Data were analysed following the intention-to-treat principle. Each group showed improved HHIE scores over time and did not differ significantly from each other. The intervention group showed significantly greater improvement compared with the control group for the CSS total and the non-verbal subscale scores. The intervention group and control group were also subdivided into two age groups: 20–59 years and 60–80 years. Significantly better improvement on the CSS total and non-verbal subscale scores was found in the older group compared with the younger participants. CONCLUSIONS: This study indicates that participants in an internet-based intervention applied in general clinical practice showed improved self-reported communication skills compared with a control group. Receiving a full intervention was not more effective in improving self-reported hearing problems than receiving just one element of the internet-based intervention. TRIAL REGISTRATION NUMBER: This trial is registered at ClinicalTrals.gov, NCT01837550; results.